Pengaruh Media Pembelajaran Berbasis Macromedia Flash Terhadap Motivasi Belajar Siswa Kelas IV B SDN 1 Rumak Kecamatan Kediri Tahun Pelajaran 2018/2019 - Lina Nida Zulfa; Ida Ermiana; Lalu Hamdian Affandi (Indonesian Journal of Elementary and Childhood Education, 2020)
This study aimed to determine the effect of the use of Macromedia Flash-based media on the learning motivation of class IV B students at SDN 1 Rumak in Kediri in 2018/2019. The results of this study were expected to be useful theoretically and practically. This type of research is an experimental study with repeated treatment research design. The subjects in this study were students of class IV B SDN 1 Rumak. Data collection methods are questionnaires and observations. Questionnaire is used to obtain data related to student motivation, while observation is used to obtain data on the performance of learning conducted by the teacher. The data obtained were then analyzed using the Anova repeated measure formula to determine whether there is an influence of the use of Macromedia Flash media on student motivation. Based on the repeated measure ANOVA test results obtained a significance number of 0,000, which means less than 0.05. This shows that H0 is rejected Ha is declared acceptable. Then it can be concluded that the Macromedia Flash media influences the learning motivation of class IV B SDN 1 Rumak Kediri District in 2018/2019.